Conditioning Native Telenomus and Trissolcus (Hymenoptera: Scelionidae) Egg Parasitoids to Recognize the Exotic Brown Marmorated Stink Bug (Heteroptera: Pentatomidae: Halyomorpha halys). Issue 1 (8th January 2019) - Tognon, R; Aldrich, J R; Sant'Ana, J; Zalom, F G
Abstract: Halyomorpha halys (Stål) (Heteroptera: Pentatomidae), the brown marmorated stink bug (BMSB), is a polyphagous fruit and vegetable pest from eastern Asia and now invasive in the United States and Europe. Earlier research revealed that the main volatile from hexane egg extracts of a western North American pentatomid, Euschistus conspersus Uhler, to which two native scelionid egg parasitoids, Telenomus podisi Ashmead and Trissolcus erugatus Johnson are highly attracted, was methyl (2 E, 4 Z )-2, 4-decadienoate, the major component of the conspecific male-produced aggregation pheromone. Conversely, extracts of BMSB eggs lacked the male-produced sesquiterpenoid H. halys pheromone components but contained C16, 18, 20 aldehydes (hexadecanal, octadecanal, and eicosanal); both egg-surface extracts of BMSB eggs and the C16, 18, 20 synthetic aldehyde blend repelled the female parasitoids. The goal of the present research was to manipulate egg-surface volatiles to induce the scelionid egg parasitoids to adopt BMSB eggs as a host. Here it was demonstrated that individual females of both parasitoids could be conditioned to H. halys egg-surface aldehydes in Y-tube olfactometer experiments, and this positive memory lasted 3–4 d. Furthermore, conditioned wasps successfully parasitized fresh H. halys eggs in no choice tests, and their offspring continued to successfully parasitize fresh H. halys eggs for 2–3 more generations. Eventually, both the individual and generational memories faded. Unconditioned female parasitoids were not attracted to H. halys egg extract or the synthetic blend of egg-surface aldehydes, nor did they parasitize BMSB eggs. Theoretical and practical implications of the research are discussed in the contexts of Hopkins' host selection principle, biological control, and instinct evolution.